Entomopathogenic nematodes and their symbiotic bacteria: from genes to field uses - Tarasco, Eustachio; Fanelli, Elena; Salvemini, Carlo; El-Khoury, Yara; Troccoli, Alberto; Vovlas, Alessio; De Luca, Francesca (Frontiers in Insect Science, 2023)
The definition "microbial control" has been used to describe the use of microbial pathogens (bacteria, viruses, fungi) or entomopathogenic nematodes (EPNs) to control various insect pest populations.EPNs are among one of the best biocontrol agents with great development in the last decades and many surveys have been conducted all over the world to get EPNs that may have potential in management of insect pests. For nematodes, the term "entomopathogenic" means causing disease to insects and is used in reference mainly to the bacterial symbionts of Steinernema and Heterorhabditis, Xenorhabdus and Photorhabdus respectively, which cause EPNs infectivity. A compendium of our multiannual experiences on EPNs' surveys, collection, identification, characterization and use in agro-forestry ecosystems is reported here to testify and demonstrate once again that the biological control with EPNs is possible and offers many advantages over chemicals as end-user safety, minimal damage to natural enemies and lack of environmental pollution, essential conditions for an IPM advanced strategy.